2022
DOI: 10.3389/fonc.2022.917353
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite stable metastatic colorectal cancer without liver metastasis may be preferred population for regorafenib or fruquintinib plus sintilimab as third-line or above therapy:A real-world study

Abstract: ObjectivesThe antitumor activity of nivolumab plus regorafenib in colorectal cancer from a phase Ib REGONIVO study is encouraging. The present study was conducted to evaluate the efficacy and safety of regorafenib or fruquintinib plus sintilimab as third-line or above therapy in patients with microsatellite stable (MSS) metastatic colorectal cancer.MethodsPatients with MSS metastatic colorectal cancer who have failed from prior treatment and received regorafenib or fruquintinib plus sintilimab as third-line or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In retrospective analyses, ICIs alone or in combination with other agents were reported to have improved outcomes in patients without LM for both MSI-H-dMMR and MSS-pMMR groups and in both first-line or refractory settings. [17][18][19][20] In the recently reported LEAP-017 study, 10 pembrolizumab and lenvatinib produced improved OS, PFS, and difference in overall response rate in patients without LM compared with investigators' choice of regorafenib or trifluridine and tiparicil. In addition to ICIs, the presence of LM may confer resistance to other immune-modulating agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In retrospective analyses, ICIs alone or in combination with other agents were reported to have improved outcomes in patients without LM for both MSI-H-dMMR and MSS-pMMR groups and in both first-line or refractory settings. [17][18][19][20] In the recently reported LEAP-017 study, 10 pembrolizumab and lenvatinib produced improved OS, PFS, and difference in overall response rate in patients without LM compared with investigators' choice of regorafenib or trifluridine and tiparicil. In addition to ICIs, the presence of LM may confer resistance to other immune-modulating agents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of the lack of efficacy of ICIs in patients with LM and advanced colorectal cancer are from single-arm phases 1 and 2 studies 7,16,21 or retrospective case series with a limited number of patients. [17][18][19][20] The current analysis was based on a randomized phase 2 study with a control arm of BSC. Our findings are consistent with those from the recently reported randomized phase 3 LEAP-017 study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2021 ASCO Meeting Abstract revealed that the objective response rate (ORR) was 27.3% and the PFS was 6.9 months in the fruquintinib 5-mg group, though it was a phase Ib/II study of the fruquintinib and sintilimab combination for advanced CRC ( 7 ). Caiyun Nie suggested that patients with MSS mCRC without liver metastasis responded well to the fruquintinib plus sintilimab regimen (ORR: 21.4%) ( 8 ). We recommend the combination of fruquitinib and sintilimab for the patient based on recent clinical trials, and our center has received several successful treatment cases.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study aimed to evaluate the efficacy and safety of combining regorafenib or fruquintinib with sintilimab in patients with MSS mCRC. Subgroup analysis revealed that NLM patients responded more positively to this combined regimen than LM patients (ORR: 21.4% vs. 9.1%) and achieved improved OS (26 vs. 10.0 months, P=0.016) ( 28 ). Organ sites have exhibited differential responses, with lymph node and LM among the most and least responsive, respectively ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%